2010
DOI: 10.1002/micr.20799
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration and repair of peripheral nerves with different biomaterials: Review

Abstract: Peripheral nerve injury may cause gaps between the nerve stumps. Axonal proliferation in nerve conduits is limited to 10-15 mm. Most of the supportive research has been done on rat or mouse models which are different from humans. Herein we review autografts and biomaterials which are commonly used for nerve gap repair and their respective outcomes. Nerve autografting has been the first choice for repairing peripheral nerve gaps. However, it has been demonstrated experimentally that tissue engineered tubes can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
153
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(158 citation statements)
references
References 166 publications
0
153
0
2
Order By: Relevance
“…2 PEG solution therapy combined with nerve tubes demonstrates a statistically significant improvement in foot fault asymmetry score at weeks 1, 2, and 3 (p=0.007, p=0.01, and p=0.006 two-tailed t test). N=8 for PEG group and N=7 for control group Nerve tubes were selected for use in comparison to microsuture because collagen conduits have demonstrated improved regeneration when utilized to repair nerve gaps [9,12,23,26,30]. For the purposes of this study, we used a collagen tube to prevent microsuture placement at the site of nerve repair and as a conduit for delivery of solutions.…”
Section: Discussionmentioning
confidence: 99%
“…2 PEG solution therapy combined with nerve tubes demonstrates a statistically significant improvement in foot fault asymmetry score at weeks 1, 2, and 3 (p=0.007, p=0.01, and p=0.006 two-tailed t test). N=8 for PEG group and N=7 for control group Nerve tubes were selected for use in comparison to microsuture because collagen conduits have demonstrated improved regeneration when utilized to repair nerve gaps [9,12,23,26,30]. For the purposes of this study, we used a collagen tube to prevent microsuture placement at the site of nerve repair and as a conduit for delivery of solutions.…”
Section: Discussionmentioning
confidence: 99%
“…1,4 Experimen-tal research on rat demonstrated that filling the veins with fresh muscle fibers allow to obtain nerve regeneration that similar to that observed with nerve autografting. 22,23 Muscle fibers avoid conduit's collapse and promote axo-nal regeneration and Schwann cell migration by means of basal lamina scaffolds.…”
Section: Discussionmentioning
confidence: 70%
“…1,5,13 Among the various biological and synthetic surgical tech-niques for nerve reconstruction, muscle-vein-combined conduits offer some important advantages: i) surgery was almost always performed in regional anesthesia allowing to harvest muscle tissue and veins, necessary for conduit preparation, from the same surgical field of nerve repair or just nearby to it; ii) however, donor sensory nerves, otherwise required to harvest a autograft for nerve repair, were preserved avoiding donor site morbidity 29 ; iii) the conduits were prepared according to reconstructive needs related to nerve size and defect length; iv) the costs for buying an artificial conduit were avoided. The latter point, however, deserves particular mention as, whereas autologous biological tissues clearly are appa-rently cost-free in comparison to artificial conduits on the market, their preparation requires additional operational room time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological tubulization has received much attention over the last century and the best results have been obtained using veins and skeletal muscle tissue (Chiu and Strauch, 1990;Pereira et al, 1991;Geuna et al, 2004;Tos et al, 2007). Also the use of a non biological conduit for nerve repair (synthetic tubulization), a strat-egy that was first attempted by Payr already in 1900, has recently seen a tremendous development due to the potential commercial spin-off of biomaterials for clinical applications (Luis et al, 2007;Siemionow et al, 2010).…”
Section: Tissue Engineering Of Peripheral Nervesmentioning
confidence: 99%